Busthanul Arifin's Thoughts and Role in the Law on Religious Courts and the Compilation of Islamic Law in Indonesia - Muhammad Fadhlan Is (Jurnal Hukum Keluarga, 2024)
One of the successes in eliminating disputes regarding Islamic law in Indonesian society was the formulation of the Compilation of Islamic Law in the late 80s. Until now, KHI remains the main guide and reference, especially for Muslims throughout Indonesia. History records that success in efforts to formulate KHI has been overshadowed by competition between several Islamic legal schools of thought, especially at that time the majority of Indonesian Muslims adhered to the Shafi'iyah school of thought, but many offers emerged to absorb Customary law and BW. In this research the author will explain Prof. Bustanul Arifin's ideas and efforts regarding the importance of Islamic legal legislation during the formulation of the Compilation of Islamic Law in the New Order era. The results of the author's research: Busthanul Arifin is a sincere hard worker and a person who is consistent with his religion. He is also good at carrying himself. With his intelligence, Busthanul succeeded in occupying the position of Supreme Court Judge at the age of 38. And when the KHI was formulated he served as Junior Chair for Environmental Affairs for the Religious Courts of the Supreme Court. Researchers found that the strongest initial initiator of KHI was Busthanul Arifin. He was also the first to use the term Compilation, as legal politics, Bustanul Arifin as the person who created the PA Bill, in his struggle he often faced obstacles and obstacles, but because of his and his team's persistence in approaching academics and ulama, taking a formal political process, constitution, DPR-RI, Supreme Court and with the government in power at that time, the PA Bill was finally passed into law in 1989.